Pengaruh Penggunaan Media Flahscard dalam Model Pembelajaran STAD Terhadap Hasil Belajar Siswa pada Materi Struktur Atom Keunggulan Nanomaterial Kelas X SMAN 16 Samarinda - Siti Marwah Multiana Sapitri; Maasje C. Watulingas; H. Usman (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
In the era of education that continues to develop, innovations in learning methods are very important to improve students' memory, one of which is flahcard media. Flashcard media is a medium that can help improve students' memory in a simple way so that students are interested and do not feel bored during the lesson being delivered. This study aims to determine the influence of the use of flahshcard media in the STAD learning model on student learning outcomes on atomic structure materials and the advantages of nanomaterials in class X of SMA Negeri 16 Samarinda. The type of research is Quasi Experimental Design with a nonequivalent Post-test Only Control Group Design. Class X.2 as an experimental class with the STAD learning model with flashcard media and class X.6 as a control class with the STAD learning model. The initial test was carried out first where the normality test and the t-test. The results of the t-test showed that there was no difference in absorption between the two classes. Data collection uses post tests and daily tests as well as observation sheets for teachers and students. The results of this study show that the learning outcomes of students in the experimental class and control class are obtained Sig.(2-tailed) of 0.000 < 0.05, then Ha is accepted. Based on this study, it can be concluded that there is an influence of the use of flashcard media in the STAD learning model on student learning outcomes on the atomic structure material of the excellence of nanomaterials in class X of SMAN 16 Samarinda.